ANALISIS SISTEM KERJA PRODUK SMOCK MENGGUNAKAN STUDI WAKTU DAN GERAKAN (STUDI KASUS PADA QUALITY CONTROL AND PACKING DEPARTMENT PT ACEPLAS INDONESIA) - Rahel Putri Sayekti; Andi Erna Mulyana (JOURNAL OF APPLIED BUSINESS ADMINISTRATION, 2019)
For made to order company such as PT Aceplas Indonesia, meet the demand with the right quantity and quality is important. But unfortunately, the company was having trouble working part-time on QC and Packing which is one of the key delivery occurrences. Therefore, conducted an analysis of the work system by using time and motion study to find out the root of the problems that exist. From the results of the study obtained six principles of motion economy that does not match the work system. From a working system that is not suitable, a new work system design is made that is more in line with the economic motion. The results obtained that the new work system that adapts to the motion economy principle have smaller working time amounted to 88% for sealing and 28% for packing.